The incredible journey - Burnford, Sheila, 1918-1984; Burger, Carl, 1888-1967 (New York : Yearling Book, 2018)
A doughty young Labrador retriever, a roguish bull terrier, and an indomitable Siamese cat set out through the Canadian wilderness to make their way home to the family they love.
Ages 8-12.
Keywords: Animals -- Juvenile fiction; Animal fiction